Innate and humoral recognition of the products of cell death: differential antigenicity and immunogenicity in lupus. (5th December 2016) - Arora, P; Malik, M; Sachdeva, R; Saxena, L; Das, J; Ramachandran, V G; Pal, R
Summary: While apoptotic debris is believed to constitute the original antigenic insult in lupus (which is characterized by a time-dependent diversification of autoreactivity), whether such debris and autoantibodies specifically recognizing its constituents mediate differential effects on innate and humoral responses in lupus-prone mice is currently unknown. Apoptotic blebs (as opposed to cellular lysate) enhanced preferentially the maturation of dendritic cells (DCs) from bone marrow precursors drawn from lupus-prone mice. Murine, somatically mutated, apoptotic cell-reactive immunoglobulin (Ig)G monoclonal antibodies demonstrated enhanced recognition of DCs and also displayed a prominent lupus strain-specific bias in mediating DC maturation. Further, immunization of such antibodies specifically in lupus-prone mice resulted in widespread humoral autoreactivity; hypergammaglobulinaemia (a hallmark of systemic autoimmunity) was observed, accompanied by enhanced antibody titres to cellular moieties. Induced antibodies recognized antigens distinct from those recognized by the antibodies employed for immunization; in particular, nephritis-associated anti-double stranded (ds) DNA antibodies and neonatal lupus-associated anti-Ro60 antibodies were elicited by a non-dsDNA, non-Ro60 reactive antibody, and Sm was a favoured target. Further, only in lupus-prone mice did such immunization enhance the kinetics of humoral anti-self responses, resulting in the advanced onset of glomerulosclerosis. These studies reveal that preferential innate and humoral recognition of the products of cell death in a lupus milieu influence the indices associated with autoimmune pathology. Graphical Abstract: